Increasing Antioxidant Activity and Organoleptic Properties of Soursop Leaf Tea (Annona muricata Linn.) by Adding Cinnamon Powder (Cinnamomum burmanni) - Indarto, Indarto; Astuti, Salima Duwi; Rudini, Mahmud; Pambudi, Wisnu (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2020)
Soursop leaf tea is a health drink that contains steroid compounds, terpenoids, flavonoids, kumari, tannins, and alkaloids. The flavonoids and tannins in soursop leaves act as antioxidants. Since it has an unpleasant aroma, cinnamon is added to add scent and flavor. This study aimed to determine the effect of cinnamon powder on the soursop leaf tea's antioxidant activity. This study employed the completely randomized design method (CRD) with two factors: the soursop leaves and cinnamon powder concentrations. This study consisted of four treatments, namely SP0 (100% soursop leaves), SP1 (90% soursop leaves and 10% cinnamon powder), SP2 (80% soursop leaves and 20% cinnamon powder), and SP3 (70% soursop leaves and 30% cinnamon powder) within three repetitions. The proximate test was focused on antioxidant activity analyzed by ANOVA at α = 5%. The organoleptic test covered the color, taste, aroma, and other overall preferences by qualitative descriptive tests. The results showed that the highest antioxidant (29.19%) could be found in the SP3 sample (70% soursop leaves and 30% cinnamon powder), while the preferred organoleptic test was the SP2 sample.